An analog of the rolle theorem for differential operators and $L$-spline interpolation - Novikov, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
An analog of the Rolle theorem is established for linear differential operators with continuous periodic coefficients. By using this result, exact values of the deviations of interpolational $L$-splines are obtained on certain classes of functions given by a linear differential operator.